Novel Ketoconazole-Loaded Niosomal Gel with Carbamide for Enhanced Topical Delivery and Skin Hydration in Fungal Infections - Prajitha Biju; Manjunath M. Shenoy; Rouchelle Tellis; Ramesh Bhat; Ranajit Das; Ashwini Prabhu; Mohammed Gulzar Ahmed; Vivek Ghate (Journal of Pharmaceutical Innovation, 2025)

Distinct metabolic signatures in blood plasma of bisphenol A–exposed women with polycystic ovarian syndrome - Navya B. Prabhu; Sampara Vasishta; Shashikala K. Bhat; Manjunath B. Joshi; Shama Prasada Kabekkodu; Kapaettu Satyamoorthy; Padmalatha S. Rai (Environmental Science and Pollution Research, 2023)
Polycystic ovarian syndrome (PCOS) is a complicated endocrinopathy with an unclear etiology that afflicts fertility status in women. Although the underlying causes and pathophysiology of PCOS are not completely understood, it is suspected to be driven by environmental factors as well as genetic and epigenetic factors. Bisphenol A (BPA) is a weak estrogenic endocrine disruptor known to cause adverse reproductive outcomes in women. A growing relevance supports the notion that BPA may contribute to PCOS pathogenesis. Due to the indeterminate molecular mechanisms of BPA in PCOS endocrinopathy, we sought liquid chromatography with tandem mass spectrometry (LC–MS/MS), a metabolomics strategy that could generate a metabolic signature based on urinary BPA levels of PCOS and healthy individuals. Towards this, we examined urinary BPA levels in PCOS and healthy women by ELISA and performed univariate and chemometric analysis to distinguish metabolic patterns among high and low BPA in PCOS and healthy females, followed by pathway and biomarker analysis employing MetaboAnalyst 5.0. Our findings indicated aberrant levels of certain steroids, sphingolipids, and others, implying considerable disturbances in steroid hormone biosynthesis, linoleic, linolenic, sphingolipid metabolism, and various other pathways across target groups in comparison to healthy women with low BPA levels. Collectively, our findings provide insight into metabolic signatures of BPA-exposed PCOS women, which can potentially improve management strategies and precision medicine.

Synthesis of azabicyclo[4.2.0]octa-1,3,5-trien-8-one analogues of 1H-imidazo[4,5-c]quinoline and evaluation of their antimicrobial and anticancer activities - Reshma Kayarmar; G. K. Nagaraja; Manjunath Bhat; Prashantha Naik; K. P. Rajesh; Suchetha Shetty; T. Arulmoli (Medicinal Chemistry Research, 2014)